Student Digital Literacy: A Mini Research in 3rd grades of English Study Program IKIP PGRI Bojonegoro - Caca - Junaidi; Rinsyana Sholekah; Andri Andri; Desy Zahwa Almaghfiroh; Ayu Fitrianingsih; Ima Isnaini Taufiqur Rohmah; Fitri Aprianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
Digital literacy is an ability to understand and use information from various digital sources. This includes not only reading skills, but also being able to think critically and evaluate information found in digital media. Literacy has an important role as a basis for life increasing knowledge and skills in the community as well as adequate digital literacy are also needed by the community as a guideline using digital technology. The purpose of this research is to increase knowledge in understanding and applying digital literacy, especially in learning English, and to improve character effectively. The method used is classroom action research. The research results refer to the answers from the plans that have been made. Starting from identifying problems, analyzing, formulating actions, planning and implementing to processing data and reporting. The data will be a guideline regarding how to implement digital literacy, especially in English and is reflective in order to improve or increase digital literacy skills.